REPRESENTASI PEREMPUAN MODERN DALAM IKLAN 60 TAHUN TEMPO SCAN - ", Rumyeni; Al'Amin, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Gender issue is an old relative issue become a controversy in the society so often inflicts various interpretations and responses that is often less correct about gender. A comprehension about gender becomes a very important meaning for all circle . mainly in gender equality in society.. The figure of women is human subject who is not man who is often presented as an object by the media. There is woman and be become the commodity by the media that become an ideology in an ads on television media for representation. Social construction and culture crystallize becoming an ideology refraction gender. So that this research aims to knowing the representation of woman in advertisment 60 years tempo scan. There is the puspose of this research is to know how the representation of woman in ads 60 years tempo scan.This research uses qualitative research method. Source of data comes from the elements or the elements that be found in ads 60 years tempo scan, and also be obtained from the audiences who have watched the ads 60 years tempo scan and based on the interview by purposive sampling as the supporting data .The results of research shows that (1) the meaning of denotation , these ads represent woman in the public area is same with a man . The equality of gender in this ads is seen clearly between man and woman , it is proved that Indonesian woman is no longer think traditional that thinks the woman work at home take care of her husband and her children in the home , but woman already work professionally .(2) In connotation meaning , this ads is more emphasis on female portrait that show the nature or characteristic of woman in general , advertiser represent woman in a feminine characteristic that is had by the woman themselves .(3) The myth study of this ads is that woman and man are the same the only difference is biologically respectively , but it does not mean woman againsts their nature as woman in general . The next myth is the woman themselves is not apart her nature as a housekeeper and not apart from the domestic are . (4) In ideology study , woman traditionally is in the domestic position because many kinds of cultural factors but in this ads has a reconstruction in the domestic area to the public’s area.Keywords :Representation, ModernWoman, ads 60 Years Tempo Scan